(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the Museum’s cooperation with educational institutions,innovative forms of excursion activities and their educational significance. Also, the content of the excursions "theatrical tour", "quest tour", "Museum in a suitcase", "Skill lesson", "Recreation", "Edutainment", "Storytelling"is widely disclosed.